피질하 허혈성 혈관치매 두 아형의 SPECT 분석 - 심용수; 양동원; 김범생; 손영민; 이동근; 정용안; 손형선 (Taehan Singyŏngkwa Hakhoe chi, 2005)
Background: The brain imaging criteria for subcortical ischemic vascular dementia (SIVD), as proposed by Eurkinjuntti, incorporates the two familiar entities, “the lacunar state” and “Binswanger's disease”. However, it has not been proven whether these two subtypes of SIVD have common pathophysiological features. This study investigated the changes of the regional cerebral blood flow (rCBF) in the two subsets of SIVD. Methods: 12 SIVD patients with predominant white matter lesions, 13 patients with predominant multiple lacunar infarctions and 17 controls were evaluated. The general cognitive function and the severity of dementia were measured by using the K-MMSE and the clinical dementia rating scale. The patients simultaneously met both the NINDS-AIREN criteria for probable or possible vascular dementia (VaD) and the Eurkinjuntti's brain imaging criteria for SIVD. 99mTc-ethyl cysteinate dimmer (ECD)-SPECT was performed to measure the rCBF, and statistical parametric mapping (SPM) was applied to the objective analysis of the SPECT data. Results: SPM analysis of the SPECT images revealed that decreased rCBF in the bilateral thalami, anterior cingulated gyri, superior temporal gyri, caudate heads and left parahippocampal gyrus was significant in the patients with SVaD compared to the controls (uncorrected P=0.001). This pattern of rCBF reduction was the same in both the SIVD patients with predominant white matter lesions and with predominant lacunar infarctions. Conclusions: Our study suggests that the two subsets of SIVD proposed by Eurkinjuntti may have a common functional abnormality, and the Eurkinjuntti's criteria offers a solution for researchers to identify the more homogeneous group of VaD patients. KCI Citation Count: 0